2006
DOI: 10.1021/ar0500618
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Biology of Protein Aggregation Diseases:  Fundamental Questions and Some Answers

Abstract: Amyloid fibrils are found in association with at least two dozen fatal diseases. The tendency of numerous proteins to convert into amyloid-like fibrils poses fundamental questions for structural biology and for protein science in general. Among these are the following: What is the structure of the cross-beta spine, common to amyloid-like fibrils? Is there a sequence signature for proteins that form amyloid-like fibrils? What is the nature of the structural conversion from native to amyloid states, and do fibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
126
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(128 citation statements)
references
References 68 publications
2
126
0
Order By: Relevance
“…Several studies have indicated that polyglutamine aggregates are connected with neurodegeneration or cytotoxicity (6,7,10,11), whereas other studies have suggested that aggregate formation is either not intimately correlated with cytotoxicity (12)(13)(14)(15) or plays a protective role in cells (16). This apparent inconsistency may be caused by structural diversity of amyloid, as amyloid-forming proteins often misfold into more than 1 conformation and the phenotypic and pathologic consequence of harboring aggregates depends critically on the specific amyloid form a protein adopts (17)(18)(19)(20)(21). A striking example of this observation is the prion strain phenomenon.…”
mentioning
confidence: 99%
“…Several studies have indicated that polyglutamine aggregates are connected with neurodegeneration or cytotoxicity (6,7,10,11), whereas other studies have suggested that aggregate formation is either not intimately correlated with cytotoxicity (12)(13)(14)(15) or plays a protective role in cells (16). This apparent inconsistency may be caused by structural diversity of amyloid, as amyloid-forming proteins often misfold into more than 1 conformation and the phenotypic and pathologic consequence of harboring aggregates depends critically on the specific amyloid form a protein adopts (17)(18)(19)(20)(21). A striking example of this observation is the prion strain phenomenon.…”
mentioning
confidence: 99%
“…Amyloid fibril formation is characteristic of a variety of human disorders, including Huntington and Alzheimer diseases (1,2). In amyloid-related diseases, one or more proteins are found in fibrillar aggregates, in a non-native, highly ␤-sheetrich conformation.…”
mentioning
confidence: 99%
“…Many proteins can also be made to form amyloid fibrils in vitro. Intriguingly, there are many accounts of proteins that form amyloid-like fibrils that are not associated with pathologies (2). Whether disease-related or not, amyloid fibrils share key biochemical and biophysical characteristics, suggesting common structural features.…”
mentioning
confidence: 99%
“…Folded proteins may aggregate by domain-swapping or by interaction with their surfaces, such as the so-called "end-to-end" stacking (Bennett et al 2006;Eisenberg et al 2006;Nelson and Eisenberg 2006a,b). Because such aggregates are based on interactions between folded proteins, there is not a gross rearrangement of the protein fold, and the repetitive nature of the structure is at the suprananomolar level, contrasting the subnanomolar repetitive nature of the amyloid, which gives rise to the many potential activities of the amyloid through cooperativity effects (see above).…”
Section: The Amyloid Compared To Other Protein Aggregatesmentioning
confidence: 99%
“…It is the aim of this review to discuss the structural nature of the cross-bsheet motif in detail and put its potential actions into perspective. Eisenberg et al (2006) determined the threedimensional (3D) structures of short fibrilforming peptide segments of amyloid proteins (such as PrP, Sup35, insulin, Ab, tau, and amylin) from microcrystals by X-ray crystallography (Nelson et al 2005;Nelson and Eisenberg 2006a,b;Sawaya et al 2007). The soluble peptides are able to form microcrystals as well as amyloid fibrils.…”
mentioning
confidence: 99%